Britain's Day-flying Moths A Field Guide to the Day-flying Moths of Great Britain and Ireland, Fully Revised and Updated Second Edition - Newland, David; Still, Robert; Swash, Andy (WILDGuides, 2019)
A carefully designed and beautifully illustrated photographic guide to the moths you are most likely to see during the dayThis concise photographic field guide helps you to identify the day-flying moths most likely to be seen in Great Britain and Ireland. It combines stunning photographs, clear and authoritative text and an easy-to-use design to increase your knowledge and enjoyment of these intriguing and often colourful insects. Like butterflies, some moths fly regularly in sunshine, whereas others that usually fly at night are readily disturbed from their resting places during the day. This guide describes all of these species and features at least one photograph of each in its natural, resting pose. A brief description of each moth covers the key identification features and when and where to look for it, and includes information on its status, life history, special features and caterpillar food plants. Other sections explain how to distinguish moths from butterflies, and also provide essential information on biology, classification, habitats, gardening for moths, conservation and legislation and recording and monitoring.Individual accounts for 158 species and photos of 28 othersMore than 320 stunning photos, with every moth shown as you see itBeautifully designed, easy to use and clearly written